Evaluation of Methiorep as a Substitute for Methionine in Broiler Diets - Salome, Itoe; Dafwang, I.I.; Bawa, G.S. (International Journal of Poultry Science, 2010)
A total of 225 day old broiler chicks were used to evaluate the use of Methiorep, a herbal Methionine product, as a substitute for synthetic Methionine in broiler diets. The experiment lasted from 0-4 weeks of age. The birds were randomly allocated to 5 dietary treatments in 3 replicates of 15 birds each, giving a total of 45 birds per treatment. The 5 dietary treatments comprised diet 1 which was devoid of supplementary Methionine and Methiorep, diet 2 had 0.25% Methionine, while diets 3-5 had graded levels of 0.25, 0.5 and 1% Methiorep respectively. All diets were isocaloric and isonitrogenous. The results showed that birds fed the Methionine supplemented diet performed significantly (p